Die allokasie van die vraag na elektrisiteit met behulp van gemengde heeltallige programmering - C. A. Anderson; W. G. Klerck (South African Journal of Business Management, 1983)
– The allocation of the demand for electricity using mixed integer programmingIn this paper the authors have investigated the use of mixed integer programming to solve an allocation problem that exists in the Electricity Department of the Pretoria Municipality. In the Pretoria supply area the demand for electricity is provided for by using the municipal power stations Rooiwal and Pretoria West and by obtaining power from Escom. Every year the Electricity Department must decide how the monthly demand (12 months ahead) for electricity must be allocated between their own power stations and the supply from Escom.The allocation must be done in such a way that certain requirements are met. These requirements refer to the demand for electricity, the availability of the municipality's own generators, the capacity of the two power stations and a so called supply requirement laid down by Escom. A mixed integer programming model was developed in which these requirements were catered for and in which the running costs were minimized. Results obtained thus far from the model indicate that it can provide the Electricity Department with a useful tool in solving a complicated allocation problem.
Keywords: 650